FORMULASI DAN UJI EFEKTIFITAS SPRAY NABATI BERBASIS EKSTRAK DAUN PANDAN (Pandanus amaryllifolius) SEBAGAI REPELLENT SEMUT - Kristina Mulia; Putri Soleha; Sefti Dahnia; Wentri Susanti; Zabrina Wardah A.Z (University of Bengkulu, 2026)
House ants are one of the most common residential pests that can disturb comfort and potentially act as disease vectors. Repeated use of synthetic pesticides may cause negative impacts on human health and the environment; therefore, safer natural repellent alternatives are needed. This study aimed to determine the potential of pandan leaf extract (Pandanus amaryllifolius) as a repellent against black ants (Camponotus pennsylvanicus) and to identify the most effective optimum concentration. The study employed a Randomized Posttest-Only Control Group Design consisting of seven treatment groups, namely a negative control, pandan leaf extract concentrations of 5%, 10%, 15%, 20%, and 25%, and a positive control. Each treatment used 10 ants with four replications, resulting in a total sample of 280 ants. The test was conducted by observing the number of ants crossing the filter paper toward the bait within 10 minutes. Data were analyzed using the Kruskal–Wallis and Mann–Whitney U tests. The results showed that pandan leaf extract has potential as a natural repellent against black ants. The highest repellency percentage was obtained at concentrations of 15%, 20%, and 25%, each reaching 100%, while the 5% concentration showed a repellency rate of 89%. Statistical analysis indicated that all treatment groups were significantly different from the negative control (ρ < 0.05). The 20% concentration was considered the most optimal because it demonstrated high effectiveness without causing ant mortality. Therefore, pandan leaf extract has the potential to be developed as a more environmentally friendly botanical repellent for controlling domestic ants.